PENGGUNAAN TEPUNG BIJI DURIAN (Durio zibethinus Murr) SEBAGAI SUMBER ENERGI DALAM PAKAN TERHADAP PERFORMAN ITIK LOKAL JANTAN (Anas platyrhynchos) - Hasnawati, Hasnawati; Marfuah, Nuun; Sugiarto, Sugiarto (AgriSains, 2016)
The aim of this study was to determine the use effect of durian seed flour as a source of energy in the ration of the male local duck growth performance. This research was conducted in experimental cages of Animal Husbandry and Fisheries Faculty Tadulako University, using 80 ducks for 8 weeks. This study was designed using completely randomized design (CRD) with 5 treatments and 4 replications. The treatments were tested, as follows: R0 (control); R1 (5% boiled durian seed flour replacing corn in the control diet); R2 (10% boiled durian seed flour replacing corn in the control diet); R3 (5% durian seed flour without replacing corn in the control diet) and R4 (10% durian seed flour without replacing corn in the control diet) with 20% protein iso and 3,100 kcal metabolizable energy iso. Data were analyzed using analysis of diversity according to the design used and followed by honestly significant difference test. The results showed that the treatment significant effect (P <0.05) on feed consumption, body weight gain and feed conversion. Treatment composition that gives the best results, namely the R1 treatment with the use of 5% boiled durian seed flour replacing corn in the ration, with average feed consumption 5.069g; 1.100g body weight gain; and conversion of 4.61.Â Keywords: duck performance, durian seed flour, male local duck